Pengaruh Kualitas Pelayanan Petugas Check-In Counter terhadap Kepuasan Penumpang Maskapai Citilink di Bandar Udara Internasional I Gusti Ngurah Rai Bali - Ardhana, Clarista Sukma; Yudianto, Kifni (MES Bogor, 2024)
This research aims to determine the influence of service quality on passenger satisfaction on Citilink airline passenger satisfaction at I Gusti Ngurah Rai Bali. This research uses quantitative methods. The data collection technique is by distributing statements (questionnaires) to a sample of 109 respondents. The sampling technique uses the Purposive Sampling technique, namely a sampling technique with certain decisions. Hypothesis testing uses multiple regression with t test and coefficient of determination. The results of the analysis show that service quality can be seen to have a significant positive impact on passenger satisfaction on Citilink airlines amounting to 14,884 on customer satisfaction. Influence of service quality variables. The research results show that 67.1% of Citilink airline customer satisfaction is influenced by service quality which consists of five dimensions, tangible, reliability, responsiveness, assurance and empathy. The remaining 32.9% is influenced by other variables not studied such as brand image, ticket prices and discounts.